Acute bronchiolitis in infancy as risk factor for wheezing and reduced pulmonary function by seven years in Akershus County, Norway - Gulbrandsen Pål; Ufert Gunn; Rød Gisle; Farstad Teresa; Fjærli Hans-Olav; Nakstad Britt (BMC, 2005)
Abstract Background Acute viral bronchiolitis is one of the most common causes of hospitalisation during infancy in our region with respiratory syncytial virus (RSV) historically being the major causative agent. Many infants with early-life RSV bronchiolitis have sustained bronchial hyperreactivity for many years after hospitalisation and the reasons for this are probably multifactorial. The principal aim of the present study was to investigate if children hospitalised for any acute viral bronchiolitis during infancy in our region, and not only those due to RSV, had more episodes of subsequent wheezing up to age seven years and reduced lung function at that age compared to children not hospitalised for acute bronchiolitis during infancy. A secondary aim was to compare the hospitalised infants with proven RSV bronchiolitis (RS+) to the hospitalised infants with non-RSV bronchiolitis (RS-) according to the same endpoints. Methods 57 infants hospitalised at least once with acute viral bronchiolitis during two consecutive winter seasons in 1993-1994 were examined at age seven years. An age-matched control group of 64 children, who had not been hospitalised for acute viral bronchiolitis during infancy, were recruited from a local primary school. Epidemiological and clinical data were collected retrospectively from hospital discharge records and through structured clinical interviews and physical examinations at the follow-up visit. Results The children hospitalised for bronchiolitis during infancy had decreased lung function, more often wheezing episodes, current medication and follow-up for asthma at age seven years than did the age matched controls. They also had lower average birth weight and more often first order family members with asthma. We did not find significant differences between the RSV+ and RSV- groups. Conclusion Children hospitalised for early-life bronchiolitis are susceptible to recurrent wheezing and reduced pulmonary function by seven years compared to age-matched children not hospitalised for early-life bronchiolitis. We propose that prolonged bronchial hyperreactivity could follow early-life RSV negative as well as RSV positive bronchiolitis.